Environmental problems affecting health (PAHO WashingtonUS, 1990)
Examines problems such as - drinking water and sanitation; urban refuse collection; pollution of water resources; air pollution; pesticide use; management and handling of hazardous toxic wastes; accidents caused by chemical agents; food contamination; and health of workers.
Extracted from Health conditions in the Americas 1990 edition V.1.